Pengaruh Covid-19 dan IHSG Terhadap Kurs Rupiah/USD - Ahmad Eko Saputro (Politeknik Negeri Padang, 2020)
This study aims to determine the effect of Covid 19 and IHSG on the Rupiah / USD exchange rate during the COVID-19 pandemic. The data used in this study are daily data on confirmed cases of Covid 19, daily data on the IHSG and Rupiah / USD exchange rate from March 2 to April 30 2020. The results of this study are partially Covid 19 has a negative effect (coefficient value -0.128) but not significant alpha 5% (0.871> 0.05), JCI has a negative effect (coefficient value -0.542) and significant alpha 5% (0.017 <0) . , 05). However, simultaneously it affects the rupiah exchange rate (prob F-test is smaller than 5% / 0.000 <0.05) and has a contribution to the exchange rate of 94.1% (coefficient of determination R2 = 0.941)